Anti-inflammatory and Antioxidant Activities of Cucumis sativus Leaves (Bangladesh Pharmaceutical Journal, 2015)
This study was carried out to evaluate the anti-inflammatory and antioxidant activities of Cucumis sativus Linn. (Family: Cucurbitaceae) leaves. The methanolic extract of C. sativus leaves (MCS) was investigated for antiinflammatory activities in Long Evans rat model at two different doses of 150 and 250 mg/kg body weight and the effects were compared with the standard, indomethacin (10 mg/kg body weight). It exhibited highest antiinflammatory activity at the dose 250 mg/kg. In the formalin test, the extract at both doses (150 and 250 mg/kg body weight) significantly prevented the increase in volume of paw edema (P